2013
DOI: 10.1017/s1368980013001675
|View full text |Cite
|
Sign up to set email alerts
|

Association of 25-hydroxyvitamin D with Hb and lead in children: a Chinese population-based study

Abstract: Objective: To evaluate the prevalence of vitamin D deficiency and insufficiency, as well as their association with Hb and elevated blood lead levels (BLL) in children in China. Design: A cross-sectional and 1-year retrospective study. Setting: Department of Laboratory Medicine, West China Second University Hospital, Sichuan University, China. Subjects: Children aged from 6 months to 14 years living in south-west China who were taken to physical examinations (January-December 2011). Results: Of 1218 children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
(65 reference statements)
3
27
1
Order By: Relevance
“…Another 20 papers were excluded because association of interest was not evaluated, requested data were not reported, of duplicate papers of the same studies, Finally, seven studies matched the selection criteria and were suitable for our metaanalysis. [16][17][18][19][20][21][22] Three of these studies were cross-sectional, one study was a historical cohort study and three studies were case-control studies. A flow-diagram for the selection of studies to include in our meta-analysis is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 20 papers were excluded because association of interest was not evaluated, requested data were not reported, of duplicate papers of the same studies, Finally, seven studies matched the selection criteria and were suitable for our metaanalysis. [16][17][18][19][20][21][22] Three of these studies were cross-sectional, one study was a historical cohort study and three studies were case-control studies. A flow-diagram for the selection of studies to include in our meta-analysis is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Two studies originated from the United States 16,17 and one study from France. 20 The remaining four studies were from Asian countries, including: two from Korea, 18,22 one from China 19 and one from Bahrain. 21 A total of 5183 participants were included in our meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Little is currently known about the links between VD and Pb toxicity, and the available data is controversial. While polymorphisms in VDR gene have been associated with increases in blood Pb levels 27 , 28 , others have also reported significant negative correlations between blood levels of Pb and VD 29 , 30 . Additionally, numerous studies suggested that Pb enters the cytoplasm through Ca 2+ channels 31 , 32 and that Ca 2+ channel blockers resulted in lower levels of Pb in renal tissues 31 .…”
Section: Introductionmentioning
confidence: 98%
“…Our case also presented with anemia that can be explained by the fact vitamin D has a vital role in promoting erythropoietin by downregulating proinflammatory cytokines and activating the erythropoietin hormone itself [24][25][26]. Other typical features of rickets like craniotabes, dental deformities, and rachitic rosary and Harisson's groove were not present in this child.…”
Section: Discussionmentioning
confidence: 67%